« You little zit! » ou quand une sitcom américaine est génératrice d’insultes - Vincent Hugou (Anglophonia)
This study focuses on two productive constructions of insults in English: the vocative and the imperative. The corpus consists of the 261 episodes of an American sitcom, Married with Children (1987-1997), where innovative insults can be found in great quantity. Our main goal is to determine how readily the speaker comprehends an innovative insult. We assume that there are syntactic, semantic, morphological and phonological  « hints » in the newly-formed insult which better enable the retrieval of the construction on which the new form is modelled, and which thereby facilitate comprehension. We asked informants to evaluate the degree of prototypicality of these innovative insults, outside of their context of origin, in order to determine which hints are more relevant than others and if comprehension is still possible below a quantitative threshold. Results indicate that some hints are more relevant than others and that the number of hints is not a necessary condition to decode the new insult. They also often point to the insufficiency of the construction, which cannot alone convey meaning: full understanding requires recourse to context and suprasegmental factors.